Profile of drug use in Guillain Barre Syndrome (GBS) patients at "X" private hospital - Dewi, Fransiska Rosari; D, Ni Putu Desy Ratna W.; Sriasih, Ni Kadek; Riantarini, IGA. M. (Science Midwifery, 2024)
Centers of Disease Control and Prevention / CDC (2012), Guillain Barre Syndrome (GBS) is a rare disease in which a person's immune system attacks the peripheral nervous system and, if severe, paralysis can occur. The treatment the patient receives is not a cheap treatment, even if treatment is carried out too late it will cause death. This research was conducted to look at the patient profile and treatment profile of GBS patients at the "X" Private Hospital. Method: This research is observational with secondary sampling and a retrospective study on Guillain Barre Syndrome (GBS) patients in the period 1 January 2019-31 December 2022. The total population in this study was 6 patients. The profile of drug use in GBS patients that was most commonly used was specific/etiological therapy in the form of immunotherapy in 6 patients (100%); privigen (67%) and gammaras (33%). Supportive (symptomatic) therapy is in the form of 100% of neurotropics and 100% of analgesics, and 17% of complicative therapy is in the form of antibiotics. Corticosteroids used are Methylprednisolone (3x2.5 mg – 3x75 mg) IV (50%) and dexamethasone IV (4x 5 mg – 3 x 5 mg) 50%. The most common analgesics used by patients were paracetamol (3x1g) IV (100%), muscle relaxants 16% and GABA analogues 33%. The most commonly used neurotropic is Mecobalamin (3x500μg) IV 100%. GBS treatment follows therapy guidelines, and research needs to be carried out regarding the prevalence of recurrence in GBS sufferers.